The Pivotal Role of Chemical Modifications in mRNA Therapeutics - Liu, Albert; Wang, Xiao (Frontiers in Cell and Developmental Biology, 2022)
As exemplified by SARS-CoV-2 mRNA vaccines, mRNA has emerged as a disruptive technology that transform the development of vaccines and drugs by its advantages of programmability, scalability, and rapid development. These vaccines, as well as multiple other mRNA therapeutic candidates, are enabled by chemical modifications to modulate their immunogenicity, stability, and translational efficiency. Despite the importance of mRNA modifications for harnessing the full efficacy of mRNA drugs, the full breadth of potential modifications has yet to be explored. In this review, we survey the field of mRNA modifications, highlighting their ability to tune the properties of mRNAs. These include cap and tail modifications, nucleotide substitutions, and chimeric mRNAs, each of which represents a component of mRNA that can be exploited for modification. Additionally, we cover clinical and preclinical trials of the modified mRNA platform not only to illustrate the promise of modified mRNAs but also to call attention to the room for diversifying future therapeutics.